Three decades of the development of academic journals in Islamic studies in Malaysia 1977-2007 - Hashim, Roosfa; Kasan, Hasnan (Medwell Journals, 2012)
The intent of this study is to present the status and position of academic journals in Islamic Studies in this country. The exponential growth of teaching and research institutes centralizing on Islamic studies has given rise to the number of Islamic scholars in this country and prospers various research and publication endeavors. This scenario is welcome with the emergence of diverse academic journals that serve as the academic centerstage in multiple Islamic knowledge branches. The status of this journal is examined by detecting it using the library and publisher catalogues. This study documents 34 academic journals in various branches of Islamic studies and published for the past 3 decades in the period of 1977-2007.